Keterlibatan Masyarakat Dalam Sistem Penegakan Hukum Terhadap Lingkungan Di Indonesia - Sendow, Martha Mareyke; Wowor, Karel; Ginting, Grenaldo (Sam Ratulangi University, 2023)
This study aims to determine community involvement in the law enforcement system for the environment in Indonesia. The research was carried out from June to September 2020. The research data collection technique was carried out deliberately. The data used in the research is through literature studies or document studies based on secondary data. Research refers to increasing public awareness in developing the ability and willingness to manage and maintain a pristine environment against pollution and environmental destruction. Apart from its influence, the concept of development is to create physical and moral concepts on a micro basis and support environmental development with the enactment of Environmental Law No. 4 of 1982. With the attention and awareness of the environment based on legal norms, it is an effort to overcome the problems of people's lives, improve the quality of human resources in the field of comprehensive education. Law enforcement is closely related to obedience for users and implementers of laws and regulations, the community is also subject to environmental laws.